Integrated disease management of early blight of tomato - Devi, P Rama; Prasadji, J Krishna; Srinivas, T; Rani, Y Ashoka; Rao, G Ramachandra (Indian Journal of Plant Protection, 2020)
Investigation on tomato early blight disease management was carried out at Horticultural Research Station, Venkataramannagudem, West Godavari (dt), Andhra Pradesh during 2012-13 and 2013-14. The biological Systemic acquired resistance (SAR) inducer, Pseudomonas fluorescens and two fungicides (tebuconazole and copper oxychloride) that were found most inhibitory to Alternaria alternata in in vitro studies were evaluated in different combinations in the form of seed treatments followed by foliar sprays, seedling root dips followed by foliar sprays or foliar sprays alone. Among the combinations tested, treatments involving fungicides wereÂ superior to treatments with P. fluorescens alone either as seed treatment or seedling root dip followed by foliar sprays. Tebuconazole seed treatment followed by four foliar sprays each of tebuconazole and copper oxychloride alternatively recorded the lowest terminal disease severity (PDI=35.4%) i.e., 53.2% less than the PDI recorded in check (75.6%) and gave the maximum yield (25.7 t/ha) i.e., 86.5% increase over control and with a Benefit : Cost ratio of 1.60. Significantly higher yield (19.3 t/ha) i.e., 39.8% increase in yield compared to control (13.8 t/ha) and reduction in disease severity by 20.8% was also realized in treatment with P. fluorescens applied to seed and foliage (two sprays) followed by tebuconazole and copper oxychloride (one spray each) alternatively with significant highest Benefit : Cost ratio of 1.32 and could be a best alternative for the management of blight pathogen and for production of quality tomatoes with high returns as number of chemical sprays are minimized